Evaluación preliminar de impacto ambiental de la construcción del aeropuerto Nacional de la localidad de Calzada - Chuquijajas Carranza, Mirla Judith (2012)
This thesis research project is to evaluate the environmental baseline that is the town of Calzada, it has beco me in the last months in the high focus of May due to the implementation of a major project which is the construction ofthe Alto Mayo National Airport, and especially the current municipal government has every interest in addressing issues related to the development of the basic infrastructure of the town while the interest due on natural resources, in this regard, urges us to have to make this modest research purposes to improve air service in the Alto Mayo and particularly in the San Martín region, the same impact on the living ~onditions of the principal which often make use this type of transport. The purpose of this research is to develop the Environmental Impact Assessment for the construction of the Regional Airport that would be located in the town of Calzada, also allow adequately manage potential negative impacts of construction activities products that may be generated in different stages of the project cycle. It is important that you start to see more seriously the public need to have an air terminal in this part of the department of San Martín, as is currently the largest construction project that would run in the Alto Mayo do.